2022
DOI: 10.1186/s13054-022-04133-7
|View full text |Cite
|
Sign up to set email alerts
|

Early hyperoxia and 28-day mortality in patients on venoarterial ECMO support for refractory cardiogenic shock: a bicenter retrospective propensity score-weighted analysis

Abstract: Background The mortality rate for a patient with a refractory cardiogenic shock on venoarterial (VA) extracorporeal membrane oxygenation (ECMO) remains high, and hyperoxia might worsen this prognosis. The objective of the present study was to evaluate the association between hyperoxia and 28-day mortality in this setting. Methods We conducted a retrospective bicenter study in two French academic centers. The study population comprised adult patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 38 publications
7
30
1
Order By: Relevance
“…Even though we did not specifically measure it, our findings suggest that the retrograde aortic flow of VA ECMO was able to reach the proximal aortic arch (i.e., right radial artery). We did not find an association between hemoglobin and oxygenation, as described by some authors for VV ECMO [ 12 , 23 , 24 ]. This can be explained by the hemoglobin value, which was not very low in the patients from our cohort, and the Q EC which was high, thus maintaining oxygen delivery [ 23 ].…”
Section: Discussionsupporting
confidence: 45%
“…Even though we did not specifically measure it, our findings suggest that the retrograde aortic flow of VA ECMO was able to reach the proximal aortic arch (i.e., right radial artery). We did not find an association between hemoglobin and oxygenation, as described by some authors for VV ECMO [ 12 , 23 , 24 ]. This can be explained by the hemoglobin value, which was not very low in the patients from our cohort, and the Q EC which was high, thus maintaining oxygen delivery [ 23 ].…”
Section: Discussionsupporting
confidence: 45%
“…To the editor, We read with great interest the article by Moussa et al which illustrated the association between early hyperoxia and 28-day mortality in patients on venoarterial extracorporeal membrane oxygenation (VA-ECMO) support for refractory cardiogenic shock [1]. Hyperoxia might increase oxidative stress, leading to worse outcomes [2].…”
mentioning
confidence: 99%
“…Several observational studies have examined the association between hyperoxia during VA-ECMO and patient outcomes and the findings are inconsistent [6,[9][10][11][12]. The methodology of these studies have been highly variable and although the demonstrated effect of hyperoxia has varied a high prevalence of hyperoxia amongst VA-ECMO patients has been ubiquitous [7,[9][10][11][12].…”
mentioning
confidence: 99%
“…Patients requiring Venoarterial extracorporeal membrane oxygenation (VA-ECMO), may be at increased risk from hyperoxia due to pre-existing oxidative stress from ischemia reperfusion injury and a high prevalence of extreme hyperoxia [ 6 , 7 ]. As such the control and effect of hyperoxia exposure during VA-ECMO requires investigation.…”
mentioning
confidence: 99%